City The Influence of Financial Literacy, Lifestyle, and Self-Control on the Consumer Behavior of Students at Panca Budi Development University - Asminar Br Siagian; Aulia Aulia; Cahyo Pramono (Universitas Dehasen Bengkulu, 2026)
The study aims to analyze the influence of financial literacy, lifestyle, and self-control on the consumer behavior of students at Panca Budi Development University. This study used a quantitative approach with a causal associative approach. The population in this study were 71 Fintech Management students at Panca Budi Development University, using a saturated sampling technique, so that the entire population was included as respondents. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression, using classical assumption testing, t-tests, F-tests, and coefficients of determination using SPSS version 23.The results showed that financial literacy partially had no significant effect on consumer behavior. Meanwhile, lifestyle and self-control had a positive and significant effect on consumer behavior. Simultaneously, financial literacy, lifestyle, and self-control significantly influenced consumer behavior with an Adjusted R² value of 0.476. This means that 47.6% of the variation in consumer behavior can be explained by these three variables, while the remainder is influenced by factors outside the research model. These findings indicate that, in the context of college students, lifestyle is the dominant factor influencing consumer behavior, while financial literacy has not been able to significantly reduce the tendency to overconsume. Therefore, efforts are needed to improve financial education, along with strengthening self-control and developing more rational lifestyles to address the dynamics of consumption in the digital age.